Does Gender Affect Levels of Hyperbilirubinemia in Term Neonates - Ehtisham Hussain, Roshia Parveen, Versha Rani Rai, Shazia Mahar, Zubair Khoso, Taj Muhammad Laghari, Berkha Rani, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Hyperbilirubinemia is a common & in most1cases, benign problem in1first month of1life which is often1physiologic & intervention is not1usually1necessary. In the first week of life, about 60.0% of term & 80.0% of preterm infants have jaundice. Jaundice could lead to major side effects like kernicterus and permanent impairment.1One of the most frequent disorders requiring medical1attention in babies is neonatal jaundice. It has high levels of unconjugated1bilirubin, which can occasionally lead to kernicterus. Objective: To determine frequency of hyperbilirubinemia among neonates who present with physiological jaundice and compare the mean levels of hyperbilirubinemia among genders. Methodology: A total of 368 consecutive neonates were included. This cross-sectional study1was conducted at Department of Paediatric Medicine, NICH Karachi during June 2020 to December 2020. All pre-term or term neonates of either gender with physiological jaundice, and get admitted to pediatric medicine department were included in this study. While Neonates who did not survive first 48 hours of life, neonates who were not exclusively breast fed as determined by History were excluded from study. Blood samples1were taken from the patients and concentrations of serum total bilirubin, In the centrifuged venous samples, direct & indirect1bilirubin concentrations were determined. Serum total,1direct& indirect bilirubin was recorded for each patient. Data was analyzed using IBM. SPSS 22 on computer. Results: Mean ±SD age of neonates was 10.6±4.2 days. In distribution of gender, 214 (58.2%) were male while 154 (41.8%) were female. Mean ±SD of birth weight was 3.4±1.8 kg. Mean ±SD of birth weight was 3.4±1.8 kg with min to max 1.5 – 4.5 kg. majority 203 (55.2%) of neonates had birth weight was 1.5 – 3.0 kg. pre term delivery was done in 195 (53%) neonates while 173 (46.7%) were documented in term neonates. Hyperbilirubinemia was found in 156 (42.4%) patients. Mean levels of hyperbilirubinemia in male v/s female was noted as (12.3±3.8) and (11.5±3.4) respectively and P value found to be significant i.e. (P=0.038). Proportion of hyperbilirubinemia was significantly high 92 (52.9%) in neonates with age > 9 days (p=0.00). Advanced maternal age (>30 years) was also significantly associated with hyperbilirubinemia 88 (50.9%), (p=0.002; OR=1.9). C-section was significantly associated with hyperbilirubinemia 99 (49.3%), (p=0.003). Practical Implication: This study aims to provide an answer to the question of whether gender affects the level of hyperbilirubinemia in neonates. The rationale behind this is that because both preterm and term neonates are affected by this condition, if it is determined that one gender is more affected and experiences higher levels of bilirubinemia, neonates of that specific gender can be closely monitored and followed up in the future. Conclusion: It is to be concluded that hyperbilirubinemia is a frequent finding among neonates who present with physiological jaundice. Therefore, to correctly diagnose and treat the disease, both parents and professionals should take precautions. Keywords: 1Hyperbilirubinemia, Neonates, Jaundice, Risk Factors, Etiology, Hemolysis